Delft3D model-based estuarine suspended sediment budget with morphodynamic changes of the channel-shoal complex in a mega fluvial-tidal delta - Jie Wang; Ao Chu; Zhijun Dai; Jaap Nienhuis (Engineering Applications of Computational Fluid Mechanics)
Reduced riverine sediment supply and sea-level rise (SLR) threaten land building and ecosystem in deltas. However, the sediment-morphodynamic processes in a channel-shoal complex are not well understood. Here, based on bathymetry and the Delft3D model, geomorphic changes and suspended sediment budgets in the South Passage, Nanhui and Jiuduansha Shoal in the mega-Changjiang Delta were examined. Results reveal that with riverine suspended sediment concentration (SSC) decreased by 75%, the net sediment deposition rate was reduced from 4.20 cm/yr in 1979–1990 to 3.21 cm/yr in 1990–2003, and further declined to 2.21 cm/yr in 2003–2013 and 0.40 cm/yr in 2013–2020. Severe erosion occurred along the upper South Passage and extended toward the mouth bar. Strong accretions accumulated in the Nanhui and Jiuduansha Shoal. After river SSC declined from 0.53 kg/m3 to 0.35 kg/m3, 0.16 kg/m3, and 0.12 kg/m3, net suspended sediment deposition was lowered by 3.13%, 7.35% and 8.67%, respectively. Moreover, SLR of 5 cm, 15 cm, 25 cm, and 50 cm resulted in a further 1.11%, 4.18%, 4.16%, and 14.79% reduction in sediment trapping efficiency. Our findings highlight the strong likelihood that reduced river sediment input, SLRs and intensified anthropogenic effects will exacerbate sediment deficit and erosion in mega fluvial-tidal deltas.